2018
DOI: 10.1039/c8sc00167g
|View full text |Cite|
|
Sign up to set email alerts
|

O2-3-Aminopropyl diazeniumdiolates suppress the progression of highly metastatic triple-negative breast cancer by inhibition of microvesicle formation via nitric oxide-based epigenetic regulation

Abstract: A novel strategy to inhibit MV formation for the intervention of TNBC by NO-based epigenetic modification of miR-203/RAB22A expression is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…An additional study found that knockdown of Rab22a inhibits Bc metastasis in vivo (15). Kang et al (16) designed and synthesized O(2)-3-Aminopropyl diazeniumdiolates 3a-f, which prevents the growth and metastasis of triple negative Bc in vivo as well as in vitro by MHc-I impairing microvesicle formation by altering the expression of miR-203/Rab22a in a nitric oxide-dependent manner.…”
Section: Rab22a Is a Novel Prognostic Marker For Cell Progression In mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study found that knockdown of Rab22a inhibits Bc metastasis in vivo (15). Kang et al (16) designed and synthesized O(2)-3-Aminopropyl diazeniumdiolates 3a-f, which prevents the growth and metastasis of triple negative Bc in vivo as well as in vitro by MHc-I impairing microvesicle formation by altering the expression of miR-203/Rab22a in a nitric oxide-dependent manner.…”
Section: Rab22a Is a Novel Prognostic Marker For Cell Progression In mentioning
confidence: 99%
“…Although much of the research indicates that the Rab22a gene can function as an oncogene in several cancer models and indicates its potential therapy target (15,16), whether Rab22a may be developed as a novel prognostic biomarker in Bc is not well understood. The current study applied immunohistochemistry (IHc) staining and analyzed the association between Rab22a expression and clinicopathological features, as well as OS status.…”
Section: Rab22a Is a Novel Prognostic Marker For Cell Progression In mentioning
confidence: 99%
“…As a result, this horizontal transfer triggered the development of therapy-resistant metastases in BC ( Sansone et al, 2017a ). Furthermore, a recent study revealed that O 2 -3-Aminopropyl diazeniumdiolates 3a–f was created to markedly suppress the metastatic ability of TNBC by attenuating microvesicles formation in an NO-dependent manner ( Kang et al, 2018 ). Welte et al (2016) highlighted that the mTOR pathway promoted G-Colony-stimulating factors expression in preclinical models of BC which further resulted in immunosuppressive tumor microenvironment.…”
Section: The Effects Of Exosomes In the Breast Cancer Tumor Microenvironmentmentioning
confidence: 99%
“…The NO donor, CAP-NO, inhibited the basal and cytokine-stimulated adhesion of human colorectal cancer cells HT-29 to endothelial cells by inhibiting the expression of adhesion proteins ELAM-1, ICAM-1, and particularly VCAM-1 (Lu et al, 2014). NO donors inhibits the adhesion of MDA-MB231 cells to HUVEC stimulated by IL-1β and the transmigration of breast cancer cells across the lung microvascular endothelium (Kang et al, 2018;Stojak et al, 2018). This effect was mediated by a decrease in ICAM-1 expression.…”
Section: No and Tumor Cell Adhesionmentioning
confidence: 99%